Influence of preservation length of the sample on the performance of complete blood count (CBC) in rats - Azad, Nilima Rubaba; Ali, Md Mottaleb; Haque, Md Iqramul; Sujan, Khaled Mahmud; Islam, Kazi Rafiqul; Miah, Mohamma Alam; Islam, Md Kamrul (Asian Journal of Medical and Biological Research, 2020)
The performance of hematological tests deteriorates with the increase in the length of sample preservation. Therefore it has been an issue to characterize the maximum permissible period spent between blood collection and measurement to have the acceptable test report. From this view point, a study was undertaken to know about the effect of preservation length on complete blood count (CBC) in rat of Long Evans strain. A total of 30 samples were collected from 10 apparently healthy rats aged between 45-48 days and the blood samples were kept in commercial test tubes treated with EDTA. The test tubes containing whole blood samples were divided into three different groups based on preservation length and were allowed to keep at 4ºC for three different lengths of time viz. 2 hours, 4 hours and 6 hours until analysis. The samples were then analyzed for their complete blood count (TEC, TLC, Hb, PCV, DLC, Absolute Leukocyte Count, Red Cell Indices, RDW-SD, RDWCV, Platelet, MPV, PCT and PDW) using Sysmex XT-1800i auto hematological analyzer. Result showed that no significant change in CBC with the variation in preservation length. Based on these findings, it can be concluded that blood samples can be preserved for as long as 6 hours to have the same report obtainable when the samples are preserved at 4ºC in refrigerated condition for 2 or 4 hours. Asian J. Med. Biol. Res. March 2020, 6(1): 22-26